Review as Ritual: Maintaining and Disrupting Nuclear Deterrence through the Treaty on the Non-Proliferation of Nuclear Weapons Review Process - Vuori, Juha A. (Oxford University Press (OUP), 2026)
The article uses ritual action as an approach to analyze the Treaty on the Non-Proliferation of Nuclear Weapons (NPT) and its review process as (1) claims of providing solutions to problems that involve liminal boundaries and uncontrollable forces (nuclear war), (2) rooted in expert diplomatic practice (regime formation), (3) identifying evil and providing boundaries to it (securitization), and (4) reifying social processes and political structures (international stratification). The argument is that the ritual of the NPT review is involved in maintaining the nuclear order that has sets of norms, values, and social institutions, yet has also opened a new venue for disrupting the sacrosanct status of nuclear deterrence. The NPT’s review ritual has worked to internalize deterrence, strategic stability, and incremental disarmament as the only “realistic” approach to nuclear weapon possession in addition to professing the norm of non-proliferation as an unassailable public good. At the same time, the ritual provides for a glimpse of the possible through article VI of the NPT that commits nuclear weapon states to disarmament. This is the unattainable that saves the face of those in a subjugated position in the hierarchy established by the treaty. The article shows how the high politics world of nuclear diplomacy is not immune or devoid of things like emotion management or the maintenance of identities and social orders. Indeed, many human actions contain both ritual and instrumental elements, and one can mask as the other, which I argue to be the case with deterrence policies and practices.